Novel cell-based assay for detection of thyroid receptor beta-interacting environmental contaminants. (10th August 2016) - Stavreva, Diana A.; Varticovski, Lyuba; Levkova, Ludmila; George, Anuja A.; Davis, Luke; Pegoraro, Gianluca; Blazer, Vicki; Iwanowicz, Luke; Hager, Gordon L.
Abstract: Even though the presence of endocrine disrupting chemicals (EDCs) with thyroid hormone (TH)-like activities in the environment is a major health concern, the methods for their efficient detection and monitoring are still limited. Here we describe a novel cell assay, based on the translocation of a green fluorescent protein (GFP)—tagged chimeric molecule of glucocorticoid receptor (GR) and the thyroid receptor beta (TRβ) from the cytoplasm to the nucleus in the presence of TR ligands. Unlike the constitutively nuclear TRβ, this GFP-GR-TRβ chimera is cytoplasmic in the absence of hormone while translocating to the nucleus in a time- and concentration-dependent manner upon stimulation with triiodothyronine (T3) and thyroid hormone analogue, TRIAC, while the reverse triiodothyronine (3, 3′, 5′-triiodothyronine, or rT3) was inactive. Moreover, GFP-GR-TRβ chimera does not show any cross-reactivity with the GR-activating hormones, thus providing a clean system for the screening of TR beta-interacting EDCs. Using this assay, we demonstrated that Bisphenol A (BPA) and 3, 3′, 5, 5′-Tetrabromobisphenol (TBBPA) induced GFP-GR-TRβ translocation at micro molar concentrations. We screened over 100 concentrated water samples from different geographic locations in the United States and detected a low, but reproducible contamination in 53% of the samples. This system provides a novel high-throughput approach for screening for endocrine disrupting chemicals (EDCs) interacting with TR beta.